Microplastics in Sumba waters, East Nusa Tenggara. (June 2018) - Cordova, M R; Hernawan, U E
Abstract: The accumulation of plastic debris in the oceans has been widely recognized as a threat to marine environment. A recent study estimated that Indonesia is one of the biggest sources of plastic wastes in the ocean, but directly-measured abundance data from the seawater in Indonesia is lacking. We documented the abundance and distribution of microplastics (size <5mm) in sub-surface seawaters of Sumba, a pristine region in Indonesia. Water samples were collected from 5 m, 50 m, 100 m, 300 m depth and near the sea bottom. Samples were examined for microplastics using flotation and filtration methods. We found microplastic in all sampling locations, consisting of fibers (45.45%), granules (36.36%) and other plastic form (18.18%). Most of microplastic particles were found at water depths less than 100 m (81.82%), which was the thermocline area. Our finding corroborates the believe that plastics has widely invaded marine environment in different parts of the seas and oceans, including pristine, remote, and unknown areas.